Insight into the use of ionic liquid-based polymer electrolyte for super capacitor application. (February 2023) - Bello, Usman Yusuf; Kumar, Sushant; Singh, Pramod K; Kakroo, Sunanda; Madkhli, Aysh Y; Singh, Shruti; Faiz Norrahim, Mohd N; Singh, Abhimanyu
In this study, we are presenting the recent progress toward PEO-based polymer electrolytes doped with low viscosity ionic liquids with a strong emphasis on ionic liquid doped-in polymer electrolytes for energy storage applications, particularly towards electric double layer capacitors. The reliable transmission mechanism suggested by previous researchers to address the increasing trend in transport properties is ascertained with a sharp sense of the presence of different concentrations of interaction, i.e. polymer ionic liquid was also presented in detail.